Public Engagement and Green Walls in Urban Environments - Zunaira Naeem; Muhammad Waheed (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research investigates the health and well-being implications of integrating indoor vertical gardens within the context of green buildings. With a growing emphasis on sustainable architecture, incorporating living green elements into indoor spaces has become a prominent trend. This study employs a multidisciplinary approach, combining aspects of environmental psychology, indoor air quality analysis, and occupant health assessments. A green wall is an option for sustainable urban development as there is no vacant space in the urban mix. The study explores the innovative concept of green walls within the realms of ecology, horticulture, and architecture. Focusing on urban design, the research aims to recognize green walls as a distinctive element contributing to urban renewal. The primary objective is to highlight the advantages of incorporating green walls in enhancing the city's aesthetic appeal, particularly in large urban settings. The study aims to present the various ways that green walls are used in urban design while offering workable solutions through examples of actual buildings